The social-emotional development of orphan children in residential homes: care workers' perspective - Abdulla, Fatima (My University, 2018)
Many children around the world are orphaned as a result of war, natural disasters, poverty, and epidemics such as AIDS. As a result of being orphaned, children’s social-emotional development is affected. The researcher therefore set out to explore care workers’ perceptions on the social-emotional development of orphaned children in residential homes and how this may be improved. The researcher also aimed to explore the relationship care workers have with orphaned children in residential homes. The researcher used qualitative methods and interviewed ten care workers who work in residential homes in the Johannesburg area (South Africa). Four of the care worker participants were male and six were female between the ages of 30 and 65 years and have cared for orphaned children between 6 and 20 years. The researcher transcribed the data verbatim and used thematic analysis to analyse the data. Ethical standards were adhered to throughout the study. The main themes that emerged from the results suggest that care workers act as a source of care and support for orphaned children in residential homes. Care workers have other duties in the residential home which may affect their responsivity to orphaned children. Care workers also report orphaned children as having difficulties expressing emotions and making friends. Moreover, care workers report that orphaned children continue to deal with the loss of their parents and may sometimes act in aggressive ways as a result. Care workers recommend that in order to improve the socialemotional development of orphaned children, there need to be more psychologists and social workers available. The findings of this study are invaluable in contributing to an increased understanding of the perceptions care workers have on the social-emotional development of orphaned children in residential homes and how their social-emotional development may be improved.
A research report submitted in partial fulfilment of the requirements for the degree of Masters in Research Psychology by Coursework and Research Report, University of the Witwatersrand
Keywords: Orphans--South Africa--Psychological aspects; Social work with children--South Africa; Child development--South Africa; Group homes for children--South Africa--Psychological aspects